OPTIMASI BIODEGRADABILITAS DAN UJI TOKSISITAS HASIL DEGRADASI SURFAKTAN LINEAR ALKILBENZENA SULFONAT (LAS) SEBAGAI BAHAN DETERJEN PEMBERSIH - Budiawan, Budiawan; Fatisa, Yuni; Khairani, Neera (Makara Journal of Science, 2009)
Optimization of Biodegradability and Toxicity Testing of Degradation Product from Linear Alkyl Benzene Sulfonate (LAS) Surfactant as Cleaning Detergent Agent. Linear Alkyl Benzene Sulfonate (LAS) is a surfactant used in laundry detergent as cleaning agent and toxic to aquatic organisms. Results shows, with the LAS concentration used (20 ppm) in medium, adaptation time and Acinetobacter sp. growth has shown better biodegradation ability than three other bacteria used Pseudomonas putida, Pseudomonas fluorescence, Bacillaria spp. Thus, Acinetobacter sp is used further for biodegradation process of LAS. Based on its biodegradation half-life using Acinetobacter sp, and with mixed culture (± 52.32% and ± 46.82% respectively) could be achieved in 4 (four) days, LAS could be categorized as a biodegradable compound. The toxicity assay is based on tetrazolium dye reduction with Rhizobium meliloti as indicator organism. LAS is more toxic than its intermediate product from biodegradation, with IC50 = 34.35 ppm, and the intermediate product, Ac and Cm, has IC50 = 446.19 ppm and 111.28 ppm respectively. Identification of intermediate products using IR and LC-MS analysis shows that the degradation product contains chemicals compounds with functional group as follows: benzene, benzoic acid, hydroxyl, and aliphatic carbons with large molecule weight. Until its half-time degradation time, LAS biodegradation process only occurs at the aliphatic carbon chain, and have not yet reached the stage of aromatic ring opening.